Analysis of Symmetry and Motion Performance of the Transmission Mechanism of Reciprocating Cutter - Wang Hao; Yin Zhihong (Jixie chuandong, 2015)
In order to keeping the furthest symmetry of the blade upper and lower moving while the reciprocating cutter of double blade running continuously,the transmission mechanism motion mode of the double blade reciprocating cutter is researched analyzed. Firstly,the principle of realizing the reciprocating cutting of the transmission mechanism is analyzed,the space- filling model of the transmission mechanism is simplified to plane double four- bar linkage mechanism model. Secondly,through analyzing the plane double four- bar linkage simplified model of transmission mechanism and calculating with the mechanical principle knowledge of the four bar linkage,the operation conditions of the furthest symmetry are obtained and the operation conditions of the furthest symmetry are proved to be reasonable and proper by the Maple program operation and the motion simulation of ADAMS. Finally,the component size determination method are obtained by analyzing the effect of component size on the movement performance based on symmetry conditions when the movement performance is optimal.